Microstructure and Microhardness Characterization of Cr3C2-SiC Coatings Produced by the Plasma Transferred Arc Method - Islak, Serkan; Eski, Ozkan; Buytoz, Soner; Karagoz, Muzaffer; Stokes, Joseph (Walter de Gruyter Gmbh, 2012)
The purpose of this work was to investigate the coatings made of Cr3C2 and SiC powder manufactured on AISI 304 stainless steel applied by the plasma transferred arc (PTA) welding process. SiC content in the produced coated layer was varied between 0-100 wt. % and the effect of SiC concentration on the microstructure and hardness of the coating was measured experimentally. SEM analyses revealed that the composite coatings had a homogeneous, nonporous, and crack-free microstructure. Dendrites and interdendrite eutectics formed on the coating layer, subject to the temperature gradient and the solidification ratio. There was a significant increase in the hardness of coating layers with the effect of the gamma-(Fe,Ni), Cr7C3, Cr23C6, Fe5C2, Cr3Si, CrSi2, Fe0.64Ni0.36, CFe15.1, C-(Fe,Cr)-Si phases formed in the microstructure. In comparison to the substrate, the microhardness of the coatings produced by PTA were 2.5-3.5 times harder.
Keywords: Wear-Resistance; Mechanical Characteristics; Corrosion Behavior; Composite Coatings; Carbon Steel; Laser; Surface; Alloy; Overlay